Moldability characteristics of 3 mol% Yttria Stabilized Zirconia feedstock for micro-powder injection molding process - Hafizawati Zakaria; Norhamidi Muhamad; Abu Bakar Sulong; Mohd Halim Irwan Ibrahim; Farhana Foudzi (Universiti Kebangsaan Malaysia, 2014)
Micro-powder injection molding (μPIM) is a promising process that may satisfy the demand on miniaturization parts to micro domain in mass production with low manufacturing cost. Three mol% yttria stabilized zirconia (YSZ) with nano-sized powder and binder system consists of polyethylene glycol (PEG), polymethyl methacrylate (PMMA) and stearic acid (SA) were used. Nano-size powders with higher surface area generally require more binder to form a feedstock. As such, determination of the optimum powder loading of the feedstock for μPIM process is important. The rheological characteristics of different YSZ feedstocks with powder loading of 52 53 and 54 vol.% were investigated in terms of flow behavior as a function of viscosity and shear rate. Fairly low values of flow behavior exponent ranging from 0.25 to 0.39 (n<1) resulted in pseudoplastic flow behavior of the examined YSZ feedstock. The 52 vol.% feedstock exhibited the lowest viscosity resulting in highest activation energy and lowest moldability index of 1.862×10-6, while the 54 vol.% feedstock regardless to its high viscosity, yielded a low activation energy of 4.14 kJ/mol and high moldability index of 4.59×10-6. Based on rheological properties obtained, a powder loading of 54 vol.% has desirable feedstock characteristics for μPIM process and exhibited molding ability for micro detail filling. The relationship between the optimum rheological properties obtained and the actual injection process was also determined. The results showed that the green parts were able to be injected without defects such as short shot or flashing.